Comparison of three approaches of Bernese periacetabular osteotomy - Luo DZ; Zhang H; Zhang WJ (Dove Medical Press, 2016)
Dianzhong Luo, Hong Zhang, Weijia Zhang Division of Joint Surgery and Sport Medicine, Department of Orthopaedics, First Affiliated Hospital of Chinese PLA General Hospital, Beijing, People’s Republic of China Background: Developmental dysplasia of the hip is a common disease and treated with various surgical approaches. Improved ilioinguinal (I-I) approach, two-incision Smith-Peterson (TSP) approach, and modified Smith-Peterson (MSP) approach are three main approaches; however, they are rarely compared. The present study compared the operative time, blood loss, intraoperative and postoperative allogeneic blood transfusion, and postoperative complications of these three different approaches. Hypothesis: Surgical approach does not influence the operation time, blood loss, and complications of periacetabular osteotomy. Level of evidence: Level III. Case–control study. Patients and methods: In a total of 101 hips of 95 cases, from February 2010 to July 2011, three different approaches of Bernese periacetabular osteotomy, I-I, TSP, and MSP, were conducted. The operation time, intraoperative bleeding, allogeneic blood transfusion, and early complications in different operation approaches were compared by a retrospective study when there were similar ages, genders, and lesions. Results: Among the three approaches, I-I had less operation time and more blood loss (P<0.05), TSP had less blood loss (P<0.05) but more complications, and MSP had less blood loss (P<0.05) and less complications. Discussion: The MSP approach is superior to the other two approaches in doing periacetabular osteotomy. Keywords: periacetabular osteotomy, operation approaches, complications